Postnephrectomy Changes in Doppler Indexes of Remnant Kidney in Unrelated Kidney Donors - Bohlouli, Abolfazl; Tarzamni, Mohammad Kazem; Zomorrodi, Afshar; Abdollahifard, Sedigeh; Hashemi, Bahram; Nezami, Nariman (Urology Journal, 2009)
Introduction: We aimed to evaluate the intralobar renal arteries indexes using the Doppler ultrasonography indexes, which have become the established method of kidney monitoring, in living unrelated kidney donors during the postnephrectomy period. Materials and Methods: In this prospective study, we evaluated and followed up 34 living unrelated kidney donors. The Doppler ultrasonography indexes, including resistive index, pulsatility index, and peak systolic velocity, along with the grey-scale ultrasonographic indexes of cortical thickness, length, and anteroposterior diameter of the kidney were determined before nephrectomy, and then, 1 week and 3 months after nephrectomy. In addition, glomerular filtration rate were assessed simultaneously. Results: The resistive index and pulsatility index did not change 1 week and 3 months after nephrectomy (P = .66 and P = .38, respectively). The peak systolic velocity at 1 week was significantly higher than its prenephrectomy value (P = .02). Also, the peak systolic velocity at 3 months was significantly higher than that prior to nephrectomy (P < .001). Indexes of the kidney size all increased during the follow-up period. The estimated glomerular filtration rate increased decreased 1 week after nephrectomy, but it reach to a level comparable with its preoperative values after 3 months. Conclusion: Results of the present study showed an increased peak systolic velocity in association with unaltered resistive index and pulsatility index in the remnant kidney of donors, during the short-term follow-up. This finding indicates the increased blood flow and kidney size in the remnant kidney of donors, following nephrectomy.